Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1177/1049732320915444
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Tourette Syndrome Caregivers With Supportive Communication

Abstract: The experiences of Tourette syndrome (TS) caregivers with supportive communication are examined in this qualitative investigation. TS is a childhood-onset neurodevelopmental disorder marked by a combination of involuntary verbal and motor tics lasting for more than 1 year. Although individuals are impacted the most by TS, the stress for caring for a child with TS takes an emotional and physical toll on the caregiver. Eleven participants shared their experiences with receiving supportive communication by taking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Qualitative studies have been conducted as follows: two in the USA ( 27 , 29 ), two in Taiwan ( 28 , 33 ), two in the UK ( 30 , 32 ), one in South Korea ( 26 ), and one in Canada ( 31 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Qualitative studies have been conducted as follows: two in the USA ( 27 , 29 ), two in Taiwan ( 28 , 33 ), two in the UK ( 30 , 32 ), one in South Korea ( 26 ), and one in Canada ( 31 ).…”
Section: Resultsmentioning
confidence: 99%
“…After screening the titles and abstracts, 22 articles were selected for full-text analysis. Finally, eight studies (26)(27)(28)(29)(30)(31)(32)(33) were included and synthesized in this review (Figure 1). The overall characteristics and extracted findings of the included studies are summarized in Tables 1, 2, respectively.…”
Section: Study and Participant Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent US study of TS caregivers found that although they received supportive communication from family, friends, and medical professionals, they also experienced communication that might have meant to be supportive but instead created distress. 2 The authors suggest that the types of messages caregivers need may depend on where they are in their 'struggle'. For example, caregivers facing a new diagnosis may need big picture messages of support and encouragement, whereas those well versed and experienced caring for a child with TS may be more interested in answers and expressions of respect from medical professionals.…”
mentioning
confidence: 99%